Concise Asymmetric Synthesis of (+)-Conocarpan and Obtusafuran - Chen, Cheng-yi; Weisel, Mark (Synlett, 2013)
The asymmetric synthesis of three natural products: (+)-conocarpan, both (+)- and (–)- obtusafuran is disclosed. The highlights of the synthesis are the enantioselective hydrogenation of prochiral ketones via dynamic kinetic resolution to afford chiral alcohols. Intramolecular ring closure via either SNAr reaction or metal-catalyzed C–O bond formation led to the construction of the trans-dihydrobenzofuran core.
Keywords: (+)-conocarpan; (+)- and (–)-obtusafuran; dynamic kinetic resolution; SNAr reaction; metal-catalyzed C–O bond formation; trans-dihydrobenzofuran; 8,5′-neolignans; 8-aryl-2,3-dihydro-benzofuran